Boundary control of a dual-output boost converter with multilevel inverter topology / Messikh Tarek - Messikh, Tarek (2017)
With the development of power electronics applications and the usage of green power technology, many multilevel converters have been proposed. These topologies are mostly used in industrial applications such as photovoltaic and wind applications. However, the problem of DC-bus balancing is the most critical point on the control side of these inverters. In this work, a dual-output boost converter (DOBC) connected to a new topology of three-level inverter is evaluated. The DOBC is controlled is such a way to obtain a regulated capacitor voltage that feed the input voltage of the three-level inverter topology regardless of load changes. The control algorithm is based on second order switching surface which provides fast dynamic response during start-up and sudden loads’ change. However, due to the need of many sensors, a sensorless boundary control method is developed. It predicts the inductor’s current of the converter by measuring only the input and output voltages of the converter. A mathematical derivation of a sensorless second-order switching surface in the state-energy plane is carried out. The performance of the proposed topology is analyzed by using Matlab/Simulink software. Steady state characteristics and large signal stability analysis are carried out for the DOBC, the sensorless control algorithm is implemented in TMS320F2812. A three-level algorithm of SVPWM is implemented in Altera DE2 board to control the three-level inverter which ensures lower hardware resource usage and satisfy the switching time criteria. A hardware prototype of the proposed topology has been developed. Experimental results show good performance and fast transient response of the proposed configuration in term of DC-bus balancing and generation of the desired output.